Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24